PENGARUH PERILAKU DAN SIKAP KEUANGAN MAHASISWA TERHADAP LITERASI KEUANGAN PADA JURUSAN AKUNTANSI FEB UNIVERSITAS PALANGKARAYA - Deo Arpasha; Rahmiati Rahmiati; Christina Fransiska (Universitas Palangka Raya, 2022)
The role of student financial behavior and attitudes is important in implementing wise financial literacy. This study aims to determine the behavior and financial attitudes of students towards financial literacy using quantitative methods. The data obtained primary with the questionnaire data collection method and the intended respondents are accounting students in semesters 4 (2020/2021) FEB Palangkaraya University. Sampling was carried out using the Slovin formula and purposive sampling technique so as to get 68 students as samples. The analytical method used is multiple linear regression and the measurement scale of the sample questionnaire value uses a Likert scale. Based on the results of partial and simultaneous regression testing, it is known that student financial behavior has no effect on student financial literacy. Students' financial attitudes have a significant effect on financial literacy. Financial attitudes are needed so that financial literacy is getting better in order to face increasingly complex financial problems in the future. From this study also, students' financial behavior and attitudes have a simultaneous effect on financial literacy, this shows financial behavior followed by the way students respond to the resources they have, leading to a wise attitude in implementing their financial literacy